Flypaper Effect of General Allocation Fund (DAU) And Human Development Index (IPM) (A Case Study In Regencies and Municipality In Bali) - Suardana, Ida Bagus Raka; Astawa, I Putu (Archives of Business Research, 2017)
Abstract